Erector spinae plane block for acute pain management of pancreatic cancer at the emergency department - Adi, Osman; Chan, Pei Fong; Ahmad, Azma Haryati; Abdul Ghani, Muhamad Rasydan; Mohd Fathil, Shahridan (Springer Nature, 2025)
Pancreatic cancer is often associated with intractable pain due to tumor invasion of surrounding neural structures and visceral organs. Conventional pain management strategies, including opioids, are often insufficient and associated with significant side effects. The erector spinae plane block (ESPB) is an inter-fascial regional anesthesia technique that can be considered in managing abdominal pain. Besides being a simple block performed, ESPB is also very effective because it provides visceral, somatic and neuropathic pain coverage. This case series highlights the potential role of ESPB as an adjunctive therapy for acute pain management of pancreatic cancer patients at the emergency department, with discussion on its technical aspect, advantages and limitations